Creative Pedagogies and Video Making: A Study on Malaysian Adolescents’ Participation in Environmental Issues - Ngu Ik Ying; Shanthi Balraj Baboo (Kajian Malaysia, 2015)
This study aims to use a creative visual approach to examine how creativity can be boosted using video making and new media technologies. It is hypothesised that adolescent participation may be optimised through exposure to creative pedagogical techniques that encourage greater freedom of expression. Examples of these techniques include dialogues, small group discussions and a redefinition of roles between researcher and participant. When offered greater autonomy, participants may be more inclined to express their views rather than giving researchers favourable answers. The findings suggested that the individual's response to environmental issues was dependent on his or her knowledge of the issue and familiarity with the given medium. When both of these factors were high, the response was relatively higher. Three themes have been identified from the data collection: (1) motivational outcomes, (2) cognitive impacts and (3) construction of a new identity as active media consumers.